Emaranhamentos de linhas discentes: os quereres na pós-graduação em educação - Echeverria, Renê Batista (2021)
This research was produced with the aim of mapping students' experiences in their relations with the Graduate Program in Education at the Federal University of São Carlos (PPGE-UFSCAR). For the processing of the mapping, references of the cartographic method were used for the creation of methodological tools through which data were produced. The initial methodological tools were designed to be operationalized in face-to-face activities with a group of volunteer students. With the advent of the pandemic, the methodological tools created for the research were adapted to the virtual context, with all meetings for data production taking place through the mediation of digital devices.